MARKETING STRATEGIES OF SMALL AND MEDIUM ENTERPRISES IN UZBEKISTAN - Raxmonberdieva Feruza Rixsiboyevna (Ecomind Press, 2025)
Marketing strategies play a crucial role in the development and sustainability of small and medium-sized enterprises (SMEs) in Uzbekistan. As the country's economy continues to integrate into global markets, SMEs must adopt effective marketing approaches to remain competitive. This paper explores various marketing strategies employed by SMEs in Uzbekistan, analyzing their effectiveness in market penetration, customer retention, and brand positioning. The study also highlights the challenges faced by SMEs in implementing these strategies, including limited financial resources, digital transformation barriers, and consumer behavior shifts. By examining contemporary marketing trends and case studies of successful SME marketing campaigns, this research provides insights into best practices for business growth in Uzbekistan. The findings suggest that SMEs should focus on digital marketing, customer relationship management, and market differentiation to achieve sustainable success.
Keywords: Marketing strategies, SMEs, Uzbekistan, digital marketing, brand positioning, market penetration, customer retention, business growth.